Foreword - GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2019)
The global economy of mid-2019 is a fragile one and needs urgent cooperation, OECD analysts said in OECD Economic Outlook issued in May 2019. Trade and policy uncertainties could significantly harm the world economy during this year and would further contribute to the growing division of people. Trade and investment have slowed drastically, especially in Europe and Asia. The confidence of companies and consumers has slowed down. In response, financial conditions have relaxed as the central banks have moved towards a more coherent monetary situation. Tax policy has provided incentives only in a few countries.